Lipid-based Drug Delivery Systems: A Promising Approach for Overcoming Bioavailability and Solubility Challenges in Drug Development - Gupta, Akash; Mittal, Vishnu; Sharma, Anjali; Barak, Aashima; Arora, Deepshi (Current Nanomedicine, 2025)
For an extended period, lipid-based drugs have been employed to enhance the effectiveness of medications. Nevertheless, the notion of using lipids as carriers for drugs remains a fascinating concept. Lipid-based drug delivery systems (LBDDS) represent a cutting-edge technology aimed at tackling the challenges associated with bioavailability and solubility of drugs that are not readily soluble in water.The primary objective of lipid-based medicine formulation is to increase its bioavailability. The use of lipids in medicine administration is a feasible concept even if it is no longer new. LBDDS is one of the newest techniques for resolving problems with low water-soluble medication solubility and bioavailability. Pharmaceuticals may be marketed successfully formulated using these formulations for parenteral, pulmonary, topical, or oral administration.This article functions as a comprehensive review of existing literature on LBDDS. It involves a thorough investigation across various databases, including PubMed, Scopus, and Web of Science, with the aim of identifying relevant research studies.LBDDS are an effective method for making poorly soluble medications (BCS Classes II & IV) more soluble and more bioavailable. This review article aims to draw attention to the importance of distinguishing between SMEDDS and SNEDDS, as well as the roles played by the many components that are needed for creating LBDDS. It also provides motivation and guts to expand the use of LBDDS on a pilot and industrial scale.Medication delivery systems based on lipids provide a wide range of possible applications by improving the bioavailability of some poorly soluble medicines and enabling the creation of physiologically well-tolerated medication formulations. Comprehending the physicochemical properties of molecules, fatty excipients, and gastrointestinal digestion is crucial for the creation of these systems. In conclusion, these delivery methods seem to have a bright future.
Keywords: drug release